2014
DOI: 10.1242/jcs.161323
|View full text |Cite
|
Sign up to set email alerts
|

INPP5E interacts with AURKA, linking phosphoinositide signalling to primary cilium stability

Abstract: Mutations in inositol polyphosphate 5-phosphatase E (INPP5E) cause the ciliopathies known as Joubert and MORM syndromes; however, the role of INPP5E in ciliary biology is not well understood. Here, we describe an interaction between INPP5E and AURKA, a centrosomal kinase that regulates mitosis and ciliary disassembly, and we show that this interaction is important for the stability of primary cilia. Furthermore, AURKA phosphorylates INPP5E and thereby increases its 5-phosphatase activity, which in turn promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 28 publications
5
99
0
Order By: Relevance
“…82 Synergistic to this effect, Inpp5E-mediated hydrolysis of PI(3,4,5)P 3 is linked to inhibition of the PI3K/AKT signaling pathway. As expected, Inpp5E-deficient cells displayed high levels of PI(3,4,5)P 3 85 and increased phospho-Akt levels; 83 further, cells expressing Joubert syndrome Inpp5E mutants also show high levels of phosphorylated Akt. 85 Recently, mouse …”
Section: Functions Of Inpp5esupporting
confidence: 76%
See 2 more Smart Citations
“…82 Synergistic to this effect, Inpp5E-mediated hydrolysis of PI(3,4,5)P 3 is linked to inhibition of the PI3K/AKT signaling pathway. As expected, Inpp5E-deficient cells displayed high levels of PI(3,4,5)P 3 85 and increased phospho-Akt levels; 83 further, cells expressing Joubert syndrome Inpp5E mutants also show high levels of phosphorylated Akt. 85 Recently, mouse …”
Section: Functions Of Inpp5esupporting
confidence: 76%
“…37,81 Inpp5E is known to be tyrosine phosphorylated by activated insulin receptor 82 and Ser/Thr-phosphorylated by Aurora kinase A (AurkA). 83 In addition to hydrolyzing the product of PI3K enzymatic activity, it has been reported that Inpp5E interacts with p85 subunit of PI3K, negatively regulating the Akt pathway, and also binds Insulin receptor substrate 2(IRS2). 82,84 A yeast two-hybrid screen identified Rab20, a Golgi-and phagosome-localized protein as the only Rab GTPase that interacts with Inpp5E.…”
Section: Inositol Polyphosphate-5′ Phosphatase E: Inpp5ementioning
confidence: 99%
See 1 more Smart Citation
“…VAV2 is a coactivator of androgen receptor (AR) and sustains AR signaling under androgen deprivation therapy (ADT) (Magani et al ., 2017); it also promotes angiogenesis and metastasis (Barrio‐Real and Kazanietz, 2012). AURKA plays a critical role in mitosis (Dominguez‐Brauer et al ., 2015; Plotnikova et al ., 2015) and promotes the development of neuroendocrine PC under ADT (Beltran et al ., 2011; Mosquera et al ., 2013). DNMT3B may regulate epigenetic events to facilitate CRPC development (Hoffmann et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…AURKA is emerging as an important regulator of mitosis and a critical player in tumorigenesis. As such, AURKA is a hotly pursued in cancer therapy (Dominguez‐Brauer et al ., 2015; Plotnikova et al ., 2015). Additionally, OIP5 is also known as Mis18β which has recently been shown to play an important role in chromatid separation during mitosis (Nardi et al ., 2016; Stellfox et al ., 2016), adding another appealing feature for its inclusion in SigMuc1NW.…”
Section: Discussionmentioning
confidence: 99%